The moral psychology of Clement of Alexandria: mosaic philosophy - Gibbons, Kathleen (Studies in philosophy and theology in late antiquity, 2017)
The mosaic law in early Christianity -- Miming Moses: Clement's self-presentation and the dependency theme -- Moses, statesman, and philosopher -- The logos of God, the problem of evil, and Clement's transformation of providence -- Right reason and the gnostic's grasp of the Mosaic law -- Clement's idiosyncratic concept of autonomy in the context of ancient thought